Comparison of discrete point and continuous data analysis for identifying performance determining factors - Richter, C.; Wheat, J.; Miller, S.; Haake, S.; Goodwill, S. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aim of this study was to compare the effectiveness in identifying performance determining factors using discrete point analysis (DPA), functional principal component analysis (fPCA) and a novel technique, analysis of characterizing phases (ACP). Twenty five vertical ground reaction force (force) curves, recorded during a vertical countermovement jump, were analyzed. Due to bi-modal force curves, DPA inappropriately identified the rate of force development as a performance determining factor. In contrast, fPCA and ACP identified the phase around the peak before and after the rapid drop in force as a performance determining factor. While both continuous techniques showed greater benefit in analyzing the captured data than DPA, ACP seems to be more reliable because it does not rely on visual observation.